Determination Of R-3-Hydroxyacylacp- Coa Transferase (Phag) Structure - Arsad, Hasni (2010)

(untitled)
R-3-hydroxyacyl-ACP-CoA transferase (PhaG) catalyzes the conversion of (R)-3- hydroxyacyl-ACP to (R)-3-hydroxyacyl-CoA derivatives, which serve as the ultimate precursor for polyhydroxyalkanoate (PHA) polymerization from unrelated substrates. PHA is a family of bioplastic that has a good potential to replace fossilbased thermoplastics because it is biodegradable. The transferase enzyme PhaG of a locally isolated strain, Pseudomonas sp. USM 4-55, was recently cloned (GeneBank accession number EU305558). Currently there is no known 3D structure with high similarity to PhaG. In order to over express, the phaG gene was cloned into expression vector pQE-30 and it was successfully overexpressed by induction with 0.5 mM IPTG in the host Escherichia coli strain SG 13009.